2016
DOI: 10.21037/tp.2016.02.01
|View full text |Cite
|
Sign up to set email alerts
|

An extremely rare case of metastatic retinoblastoma of parotids presenting as a massive swelling in a child

Abstract: Retinoblastoma (Rb) is a common childhood malignancy but bilateral Rb with metastasis to parotids is very uncommon. To the best of our knowledge, bilateral Rb metastasizing to parotids is very rare and this is the fifth such case reported in world literature till date in a 2-year-old male child who underwent exenteration of left eye for bilateral Rb and later developed recurrent metastasis to left parotid requiring parotidectomy. A year later he presented again with swelling left parotid region extending from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Five cases achieved CR, one cases achieved PR, one case died, one case lost to follow-up, one additional case was undergoing treatment. These findings suggest that systemic intravenous chemotherapy is effective for metastatic RB; moreover, focal lesions (e.g., parotid gland and cervical lymph node involvement) can undergo combined treatment with surgery and radiotherapy, consistent with previous reports [12,16] . One patient who was failed to achieve complete remission by chemotherapy alone, underwent ASCT after systemic chemotherapy; the tumor achieved CR and the patient's condition was stable, suggesting that metastatic RB may benefit from chemotherapy combined with HSCT.…”
Section: Discussionsupporting
confidence: 91%
“…Five cases achieved CR, one cases achieved PR, one case died, one case lost to follow-up, one additional case was undergoing treatment. These findings suggest that systemic intravenous chemotherapy is effective for metastatic RB; moreover, focal lesions (e.g., parotid gland and cervical lymph node involvement) can undergo combined treatment with surgery and radiotherapy, consistent with previous reports [12,16] . One patient who was failed to achieve complete remission by chemotherapy alone, underwent ASCT after systemic chemotherapy; the tumor achieved CR and the patient's condition was stable, suggesting that metastatic RB may benefit from chemotherapy combined with HSCT.…”
Section: Discussionsupporting
confidence: 91%
“…Our case shows a large intraparotid mass which has extended to the submandibular level. There have only been five previously reported cases of retinoblastoma metastasizing to parotids [ 19 22 ]. Soni et al [ 19 ] reported the first ever case in 1978, and our case is the sixth such case reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…Combined systemic IVC and radiation therapy has been successful in treating soft tissue, bone, and CNS metastases in several small-scale studies [9,[16][17][18][19]. We recommend a comprehensive management plan and personalized treatment for metastatic RB.…”
Section: Discussionmentioning
confidence: 99%